2005
DOI: 10.1111/j.1742-7843.2005.pto_96614.x
|View full text |Cite
|
Sign up to set email alerts
|

Aloe Emodin‐Induced Apoptosis in t‐HSC/Cl‐6 Cells Involves a Mitochondria‐Mediated Pathway

Abstract: The aim of our study was to clarify the apoptosis pathway induced by aloe emodin, an hydroxyanthraquinone present in aloe vera leaves, in rat hepatic stellate cells transformed by simian virus 40 (t-HSC/Cl-6), which retain the features of activated rat stellate cells. Apoptosis was determined by DNA fragmentation, caspase activity assay and western blotting analysis. Treatment of t-HSC/Cl-6 cells with 12.5, 25, or 50 mM aloe emodin inhibited t-HSC/Cl-6 cell viability in a dose-and time-dependent manner. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…AE has been shown to induce DNA damage through generation of ROS in human lung carcinoma cells (Lee et al, 2006). Studies have also suggested that AE could induce apoptosis via interruption of cell proliferation (Lian et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…AE has been shown to induce DNA damage through generation of ROS in human lung carcinoma cells (Lee et al, 2006). Studies have also suggested that AE could induce apoptosis via interruption of cell proliferation (Lian et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The extracts were successively washed with 10% NaHCO 3 , and water, and then dried over absolute MgSO 4 and filtered. The filtrate was evaporated to give a residue that was subjected to preparative TLC (5% MeOH in CH 2 Cl 2 ) to obtain compound 10 (46.9 mg, 48.3% yield, mp 97-99°C after recrystallization form acetone Table 4.…”
Section: 8-di-o-dodecylaloe-emodin (7)mentioning
confidence: 99%
“…The extracts were successively washed with 5% HCl, 10% NaHCO 3 , brine and water, and then dried over absolute MgSO 4 and filtered. The filtrate was evaporated to give a residue that was subjected to column chromatography (a gradient of 0-1% acetone in toluene) to obtain compound 16 (316 mg, 53.3%).…”
Section: 8-di-o-hexyl-15-o-tosylaloe-emodin (16)mentioning
confidence: 99%
See 2 more Smart Citations